Effects of Dissociation Water Retention on Pore Structure Disintegration in Hydrate Sediments - Yang, Liu; Wang, Shuo; Lu, Hongfeng; Liu, Ling; Sa, Rina (Frontiers in Energy Research, 2020)
During the depressurization process, natural gas hydrates (NGHs) decompose and release methane gas and water. Field experience shows that only 1% of the dissociation water is recovered, hindering the continuous pressure decline and further NGHs decomposition. The retention effect of the dissociation water on the pore structure is still unclear in NGHs sediments. In this paper, the hydrate sediment samples were tested for porosity, permeability, pore structure and clay minerals content, etc. The ions concentration change of solution was continuously measured by conductivity meter to evaluate the disintegration mechanism of sediments. The results show that the pore structure of sediments tend to disintegrate under the action of dissociation water, leading to an increase in the ions concentration of dissociation water. According to the ions concentration curve, the sediment disintegration is divided into two stages: a rapid disintegration stage and a slow disintegration stage. The rapid disintegration stage is mainly related to clay minerals. After water absorption, the illite/smectite mixed-layer expands to cause severe expansion and deformation of sediment structure. The slow disintegration stage is mainly related to the dissolution of soluble salt minerals. A large amount of salt minerals dissolve and diffuse into the dissociation water, causing the sediment skeleton to further disperse and eventually become powdery. In addition, sediment disintegration is also related to porosity, permeability, initial water content, temperature, and mineral composition. The initial water content is the main factor affecting the disintegration of sediment skeleton. Under the condition of low initial water content, the sediment skeleton disintegrates instantaneously in dissociation water. When the initial water content exceeds 30.6% 37.9%, the pore structure of sediments tends to be stable in dissociation water. Studying the effect of dissociation water on sediment pore structure is helpful to understand the mechanism of low water production and to optimize the exploitation regime of gas hydrate.